FEATURES OF THE FORMATION OF MORPHOTYPES OF YOUNG SWIMMERS IN THE PUBERTY PERIOD OF INDIVIDUAL DEVELOPMENT (Web of Technology: Multidimensional Research Journal, 2025)
At the present stage, trainers and teachers are interested in the issue of studying the patterns of morphological and functional changes occurring in the human body under the influence of sports activities, in one of the sensitive periods of ontogenesis, which is the puberty period of the body's development.